The Influence Of Human Resource Development And Innovative Work Behavior On Teacher Performamance YPC Tasikmalaya Vocational School: - Rerdiana, Diki; Barlian, Barin; Oktaviani, Nita Fauziah (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
This research was conducted to determine the Influence of human resource development and innovatif work behavior on the performance of teacher YPC vocational school Tasikmalaya. This study used a quantitative approach with Associative (Causal) research methods using data obtained directly through questionnaires distributed to 35 repondents. The technique used in this research is multiple linear regression. The results of the study indicate that: (1) human resource development and innovative work behavior simultaneously have a significant effect on Performanc teacher: (2) human resource  partially has a significant effect on  Performanc teacher: (3) innovative work behavior partially has a significant effect on  Performance teacher.